Digital Codicology on the Vatican Apostolic Library - Giuffrida, Giuliano (Digital Presentation and Preservation of Cultural and Scientific Heritage, 2025)
1650 Western manuscripts written between the year 800 AD and the year 1500 AD have been subjected to digital codicological analysis. The analysis involved approximately 600,000 high-resolution images (400 dpi), enabling the automatic extraction of 8 codicological parameters: Filling coefficient, percentage of ink on the entire page, percentage of ink in the written area, number of rows, line spacing, text height, page size, and page ratio. This study shows the evolution of these 8 parameters over the centuries, and finally a first neural network capable of automatically dating Western medieval manuscripts has been built.
Keywords: Digital Codicology; Image Analysis; Clustering; Neural Networks